Hepatoprotective Effects of Two Vitamin D3 Formulations on Letrozole-Induced Polycystic Ovary Syndrome in Female Rats: An Experimental Study - Bushra M. H. Dahak; Butheina A. Al-Amrani (University of Science and Technology, Sana’a, Yemen, 2026)
Background: Polycystic ovary syndrome (PCOS) is a complex endocrine and metabolic disorder that disrupts the hypothalamic-pituitary-ovarian axis, leading to ovarian dysfunction and hyperandrogenism. This experimental study aimed to compare the hepatoprotective effects of micellized vitamin D3 (MVD3) and conventional vitamin D3 (CVD3) compared to metformin (MET) in a rat model of letrozole (LTZ)-induced PCOS. Methods: An experimental study was conducted over 90 days using 30 healthy female albino rats with regular estrous cycles. Rats were randomly assigned to five groups (six per group): control, LTZ-induced PCOS, LTZ + MET (155 mg/kg), LTZ + CVD3 (1000 IU/kg), and LTZ + MVD3 (1000 IU/kg). PCOS was induced using oral LTZ (200 µg/day), and treatments were administered daily by gavage. Estrous cycle was assessed by vaginal cytology. Serum alanine aminotransferase (ALT), aspartate aminotransferase (AST), and alkaline phosphatase (ALP) levels were measured to evaluate hepatic function, and liver tissues were examined histopathologically after hematoxylin and eosin staining. The mean levels of liver enzymes were compared using the independent samples t-test, with significance set at P <0.05. Results: LTZ-induced PCOS caused significant elevations in serum ALT, AST, and ALP levels compared with controls (P <0.001). MET treatment partially reduced liver enzyme levels, but the mean levels remained higher than controls. In contrast, treatment with either MVD3 or CVD3 resulted in marked normalization of ALT, AST, and ALP levels compared with controls, being comparable to controls. Histopathological analysis supported these findings, showing severe hepatic structural damage in rats with LTZ-induced PCOS, partial improvement with MET, and restoration of normal hepatic architecture with MVD3 and CVD3. Conclusion: MVD3 or CVD3 markedly alleviate LTZ-induced hepatic injury in PCOS rats, outperforming MET in normalizing ALT, AST, and ALP levels and restoring hepatic architecture. These findings highlight vitamin D3 as a promising adjunct for managing PCOS-related liver injury, warranting further mechanistic and clinical studies.